Comércio de rua e sustentabilidade na cidade de fortaleza: quadrilátero da aldeota - Porto, Lívia Maria Gonçalves (2018)
The commercial activity has a close relationship with the space of public use where people meet and come into contact with the trade, streamlining the purchasing process. Aware of this relationship and the importance of trade for urban development and planning, this research intends to study the effects of trade relations with commercial activity and public spaces. The origin of commercial activity is connect to the history of humanity, where individuals met to make the exchange of their surplus production. These places became zones of meeting and leisure. Therefore the role and performance of the mercantile zones reach not only the economic as well as the social scope. The study area for this analysis is the Aldeota quadrilateral in the city of Fortaleza, which presents a diversity of retail trades, in addition to the large number of residences in its surroundings, being a mixed use district with medium density. The starting point of the research is based on the hypothesis that trade in the region has acquired inappropriate conditions for the pedestrian and concludes, showing that this urban area needs to be restructured, making it more attractive and accessible.